Mental health indicators and their lifestyle associations in German students: a gender-specific multivariable analysis - Lina Spagert; Christian Janssen; Christoph Geigl (BMC, 2022)
Abstract Background Statistics show that the number of received psychosocial counselling sessions remains at a constantly high level or has even increased since the COVID-19 pandemic situation in 2020. The objective of this work is to identify factors associated with students' mental health to improve prevention and promotion in mental health at universities. Methods The analyses were based on a cross-sectional data set collected by an online survey among 1,842 students from a German University of Applied Sciences in 2014. Descriptive statistics as well as nine different multiple linear regression models were calculated with IBM® SPSS® Statistics software. Mental health indicators used were mental health-related quality of life (mental HRQOL), depression, and anxiety, which were analysed in a gender-specific manner. Results The analyses showed that the mean of the mental HRQOL score of the SF-36 for the student sample (46.68) was lower than the values for German (48.76) or American (51.34) norm samples. A key finding was the differences in mental health indicators between male and female students. Women reported worse mental health status in comparison to men. Female gender (ß of -.09; p < 0.01), age (ß of -1.05; p < 0.01), underweight (ß of -.09; p < 0.05), smoking (ß of -.10; p < 0.05) and drug consumption (ß of -.15; p < 0.001) were negatively associated with mental health indicators. In our sample, a moderate consumption of alcohol within the female population (ß of .12; p < 0.01) and physical activity within the male sample (ß of .09; p < 0.05) were positively associated with mental health indicators. Conclusion The gender-specific differences of students' mental health and its associations could be an important result for counselling services at universities to adjust methods according to gender. Contrary to the general societal perception, students have lower mental health than a norm sample even before the pandemic. Due to the additional mental stress caused by the pandemic, it can be assumed that mental health problems have increased even more. Universities should therefore pay more attention to the mental health of their students.